CTA Annual Report 2016 - A year in review: Shaping the future - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2017)
The central role of agriculture in meeting many of the Sustainable Development Goals (SDGs) has shaped CTA’s activities over the course of 2016 and will continue to influence the organisation’s operations into the future. The articles in this annual review give a good flavour of CTA’s interventions to help smallholder producers benefit from innovations in agribusiness, finance, ICTs, climate-smart agriculture, agro-tourism, communications and knowledge management.